Reactivating Anaesthesia Services in Semporna Hospital Operating Theatre: A COVID-19 SOS Response - Abidin, Muhammad Farid Bin Zainal; Mamat, Mafeitzeral Bin; Wui, Chia Peh; Yunus, Mohd Syahfadzreen Bin (International Journal of Human and Health Sciences (IJHHS), 2021)
Introduction: The district of Semporna, Sabah faced an overwhelming surge of COVID-19 third wave by mid-September 2020. Tawau Hospital services were severely debilitated with the free flowing sick COVID-19 cases referred from Hospital Semporna as its district cluster. This was on top of the usual busy referrals of non-COVID-19 cases especially maternity related. Case Presentation & Discussion: As an ultra-red zone area, all Semporna patients were unfortunately classified as high risk COVID-19 and managed as such to ease clinical decisions. The anaesthesia services in Semporna Hospital’s operating theatre had ceased since 2007. All decisions related to possible intervention of normal labour were referred to Hospital Tawau which is 107 km away. The operating theatre was then prepared with reference to high safety international standards despite the technical drawbacks of old infrastructure facilities. The acquirement of new operation theatre (OT) equipment by Ministry of Health (MOH) due to the pandemic made the balance possible. A thorough discussion and agreement of protocols were made between the major decision makers of clinical departments from both Tawau and Semporna Hospital. A lower segment Caesarean section was performed successfully under regional anaesthesia on the 30th of October 2020 in Semporna Hospital after a 13 years’ hiatus. There were anumber of indirect benefits to the Semporna mothers and hospital with this reactivation. Conclusion: This was indeed a milestone towards upgrading the hospital for specialist services in the near future.This effort has improved the safety and quality of medical services for Semporna patients. International Journal of Human and Health Sciences Supplementary Issue: 2021 Page: S19